DAPATKAH PERSEPSI DUKUNGAN ATASAN MENGURANGI DAMPAK NEGATIF PSYCHOLOGICAL JOB DEMAND TERHADAP WORK ENGAGEMENT, SURVEI PADA KARYAWAN PT GLOBAL SAMUDRA BORNEO BANJARMASIN - Ariffin, zakhyadi (Universitas Lambung Mangkurat, 2023)
The purpose of this study was to investigate the effect of psychological job demand on work engagement and the moderating role of perceived supervisor support to reduce the impact of psychological job demand on work engagement. The survey was conducted on 64 employees from PT. Global Ocean Borneo in Banjarmasin. Data analysis used regression analysis with moderation. The findings of this study reinforce many previous studies where it has been proven that a negative psychological effect of job demand has a negative effect on work engagement. Other results show that perceived supervisor support does not play a role in reducing the effect of psychological job demand on work engagement among employees.